Clear Body, Clear Mind : the effective purification program - Hubbard, L. Ron (La Fayette Ron), 1911-1986 (Commerce, California. : Bridge Publications, Inc., 2013)
We live in a drug-oriented society. Drugs pervade our world -- from street drugs and medical drugs, to say nothing of the latest "feel-good" pharmaceuticals. Add to that the thousands of toxic substances we are exposed to on a daily basis, including household chemicals, food preservatives and pesticides, and it's easy to see that no one is immune to this crisis. Through the course of his research into the effects of drugs on the human mind, L.Ron Hubbard made a landmark discovery. Namely, that LSD appeared to remain in a person's body long after they stopped taking the drug. This breakthrough explained why someone who had used LSD in the past could suddenly reactivate a "trip" even years later. His further research revealed that many other toxic substances could also remain in the body, producing negative effects for years to come. The question remained: how can you eradicate these harmful drugs and toxins from your body? The answer is the Purification Program developed by Mr. Hubbard. With the inclusion of a precise regimen of vitamins, minerals and oils, we are able to work toward restoring the biochemical balance of the body and make it possible for the body to reconstruct itself from the damage done by drugs and other biochemical substances. - Publisher.
Introduction -- Part one : The breakthrough of the purification program. Our biochemical society -- The development of the purification program -- Part two : An overview of the purification program. A word about the program -- Exercise and sauna -- Drugs and nutritional deficiencies -- Niacin, the "educated" vitamin -- Oil : trading bad fat for good fat -- The importance of calcium and magnesium -- "Flashbacks," emotional reactions and other manifestations -- Importance of a proper schedule -- Completing the purification program -- A new life through purification -- Supplement A : Drugs and society. More on drugs and their effects -- Drugs and present time -- Drugs and learning -- Painkillers -- Supplement B : Solutions for drug addiction. Withdrawal from addictive drugs -- Supplement C : Vitamins, minerals and oil. Vitamin and mineral tables -- Calcium and magnesium : the cal-mag formula -- Oils -- Evening primrose oil -- Purification program results. Program participant successes -- Drugs, alcohol, medicines and toxins -- Exposure to hazardous materials -- Appendix. Further study -- Guide to the materials -- Addresses -- Editor's glossary of words, terms and phrases.
"A Hubbard publication."
"Editor's glossary of words, terms and phrases": pages 197-261.
Includes index.
"Further study: books & and lectures by L. Ron Hubbard": pages 175-185.
Keywords: Substance abuse -- Treatment; Detoxification (Substance abuse treatment); Nutrition; Vitamins